1998
DOI: 10.1029/98pa00070
|View full text |Cite
|
Sign up to set email alerts
|

Reevaluation of the oxygen isotopic composition of planktonic foraminifera: Experimental results and revised paleotemperature equations

Abstract: Abstract. Cultured planktonic foraminifera, Orbulina universa (symbiotic) and Globigerina bulloides (nonsymbiotic), are used to reexamine temperature:fi180 relationships at 15ø-25øC. Relationships for both species can be described by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

46
894
5
14

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 985 publications
(959 citation statements)
references
References 45 publications
46
894
5
14
Order By: Relevance
“…per practical salinity unit (psu), considerably lower than found in some previous studies (e.g., Arbuszewski et al, 2010 Lea et al (2000) using the temperature and δ 18 O relation derived for Orbulina universa (Bemis et al, 1998) of T=14.9-4.8(δ 18 Oc -δ 18 Osw), which was shown to be applicable to G.…”
Section: Methodsmentioning
confidence: 53%
See 1 more Smart Citation
“…per practical salinity unit (psu), considerably lower than found in some previous studies (e.g., Arbuszewski et al, 2010 Lea et al (2000) using the temperature and δ 18 O relation derived for Orbulina universa (Bemis et al, 1998) of T=14.9-4.8(δ 18 Oc -δ 18 Osw), which was shown to be applicable to G.…”
Section: Methodsmentioning
confidence: 53%
“…The δ 18 Osw is reported in per mil relative to the Vienna standard mean ocean water (VSMOW) by subtracting 0.27‰ from the calculated δ 18 Osw (Bemis et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…In order to calculate seawater  18 O ( 18 O SW ) as a measure of hydrologic changes, we used the  18 O:temperature equation of Bemis et al 60 :…”
Section: Age Modelsmentioning
confidence: 99%
“…While vital effects have been widely documented in biogenic carbonates such as foraminifera and ostracods (Duplessy et al, 1970;Wefer and Berger, 1991;Lea, 1993, 1996;Spero et al, 1997;Xia et al, 1997;Bemis et al, 1998;von Grafenstein et al, 1999;Chivas et al, 2002;Holmes and Chivas, 2002), almost all culture (Binz, 1987;Brandriss et al, 1998;Schmidt et al, 2001), down-core (Juillet-Leclerc and Labeyrie, 1987;Shemesh et al, 1995) and water column studies have found no clear evidence of a vital effect in δ 18 Odiatom. Recent work, however, has shown the potential for δ 18 Odiatom vital effects to exist with offsets of up to 3.51‰ (mean offset = 1.23‰, n = 25) observed between two size fractions of diatoms at Ocean Drilling …”
Section: Uncorrected Copymentioning
confidence: 99%